PERANCANGAN CORPORATE IDENTITY PT 21 EXPRESS SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Primanta, Ake Arif Radhian; Bahruddin, Muhammad; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2014)
PT. Globalindo 21 Express is one of the shipping service provider with nationwide scale. As a service provider of parcel and document delivery services, PT. 21 Express has a much larger competitors and first foray in this business. Along with the development of the times, the human need to send goods from one place to another place higher. This express PT.21 a forum for addressing the issue. but lately more and more emerging company engaged in the delivery of services to accommodate those needs. Thus it is necessary to have the strength of the company PT.21 express to be able to compete in this global era. The era where business growth faster delivery services are spread all over the country.